ANALISIS KEBIJAKAN PENDIDIKAN TERKAIT AKUNTABILITAS PEMBIAYAAN PENDIDIKAN - Hastina Hastina; Dini Ayu Safiltri; Ramadhan Ramadhan; Andika Andika (Institusi Agama Islam Negeri (IAIN) Bone, 2020)
Improving the quality of education is directly related to the role of schools as educational institutions. Management of teaching and learning in schools is very meaningful in determining student success. To achieve good quality schools, the cost of education must be managed optimally. Therefore, education funding must be considered to support the smooth learning in schools. Basically the purpose of educational funding is the implementation of the educational procaess that is in accordance with the expected learning needs of students. Accountability of education funding in schools is in the very high category, meaning that the school must be able to carry out education financing management to the fullest from the financial planning and budgeting, funding implementation, financing supervision and control or accountability.